2016
DOI: 10.17159/2310-3833/2016/v46n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Hippotherapy in occupational therapy practice

Abstract: Key words: occupational therapists, occupational therapy, hippotherapy Hippotherapy in occupational therapy practice INTRODUCTION "There is something about the outside of a horse that is good for the inside of a man." Winston ChurchillHippotherapy is a therapeutic intervention strategy in which the movement of a horse is used as part of an intervention plan. It was initially cited in the in the occupational therapy literature approximately thirty years ago 1 . There has been renewed interest in this therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Owing to hippotherapy being relatively new to Ireland, this lack of clarity requires addressing for the benefit of parents of children with disabilities and health-care professionals. In contrast, in South Africa, Govender et al (2016) report that awareness amongst occupational therapists of hippotherapy as an intervention is high, with many occupational therapists exposed to it during their studies, outlining that 42 respondents out of 47 indicated that they would consider the use of hippotherapy in the future. This suggests evidence of the profession's belief in its effectiveness as an intervention strategy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Owing to hippotherapy being relatively new to Ireland, this lack of clarity requires addressing for the benefit of parents of children with disabilities and health-care professionals. In contrast, in South Africa, Govender et al (2016) report that awareness amongst occupational therapists of hippotherapy as an intervention is high, with many occupational therapists exposed to it during their studies, outlining that 42 respondents out of 47 indicated that they would consider the use of hippotherapy in the future. This suggests evidence of the profession's belief in its effectiveness as an intervention strategy.…”
Section: Discussionmentioning
confidence: 95%
“…Hippotherapy is an emerging area of practice in paediatric occupational therapy in Ireland. With the movement of a horse being used as part of an intervention plan (Govender et al, 2016;Neill, 2018), hippotherapy is used by specially trained occupational therapy practitioners, physical therapists and speech language pathologists [American Hippotherapy Association (AHA), 2016]. Hippotherapy is used to facilitate functional gains for the purposeful manipulation of equine movement to engage neuromotor, sensory and cognitive systems to achieve functional outcomes for individuals with physical, cognitive and neuro-motor deficits (AHA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its costly price, hippotherapy is not within easy reach in Malaysia (The Edge, 2020). However, it is necessary to address this problem within the Malaysian context as the benefits of using horses for treatment have been well supported in existing research by other countries (Govender et al, 2016;Park et al, 2014;Ajzenmen et al, 2013;Guerino et al, 2015). Hence, to address the problem, the researcher needed to obtain the perspectives of Malaysian parents who are aware of hippotherapy and have sent their children with NDD for hippotherapy.…”
Section: Current Studymentioning
confidence: 99%
“…Τις τρεις τελευταίες δεκαετίες έχει ανανεωθεί το ερευνητικό αλλά και έμπρακτο ενδιαφέρον για την ιπποθεραπεία, η οποία δύναται να αποτελεί μια αξιόπιστη εναλλακτική στα προγράμματα θεραπείας ατόμων με αναπηρία με βασικό σκοπό την αποκατάσταση και τη βελτίωση της υγείας και της κοινωνικής παρουσίας τους (Govender, Barlow, & Ballim, 2016). Η ιπποθεραπεία εφαρμόζεται υπό συγκεκριμένες προϋποθέσεις, όπως, ειδικά διαμορφωμένο περιβάλλον, ειδικά εκπαιδευμένα άλογα, εξειδικευμένο επιστημονικό προσωπικό, ειδικό εξοπλισμό και τήρηση όλων των προαπαιτούμενων μιας κλασικής συνεδρίας αποκατάστασης: αξιολόγηση, πρωτόκολλο θεραπείας, στόχοι θεραπείας.…”
unclassified